Geo-hydrological hazards induced by Gorkha Earthquake 2015: A Case of Pharak area, Everest Region, Nepal (Geographical Journal of Nepal, 2020)
Nepal experienced disastrous earthquake events in 2015. The first one (magnitude of 7.8) with epicenter in Barpak, Gorkha district, occurred on 25th April 2015, followed by another event (7.3 magnitude) on 12thMay 2015, with epicenter in 19 km south east of Kodari, Sindhupalchok district. Those earthquake events induced different types of geo-hazard and they are widely distributed and caused serious damages and losses. This paper discusses the types of geo-hazards induced by these Gorkha and Sindhupalchok earthquake events and the losses and damages from those events; and the future risk from those geo-hazards in Pharak area covering 305 km2 in Solukhumbu district, Nepal. Satellite images of before and after the events were used to map landslide, debris flow, landslide dam and other geomorphic changes after earthquake. Information on the losses, damages and future risk were collected through focus group discussion, key informants’ interview, observation, and measurement. A total of 79 landslides, 13 rock falls, 5 debris flow and one site of river damming were identified and mapped. The losses and damages included private and public buildings, cultivated land, crops and other infrastructure such as trails, canals for hydropower plant. The losses and damages associated with landslide and debris flow induced by earthquake is comparatively higher than the losses and damages from other geomorphic hazards such as rock fall and landslide dam and landslide dam outburst flood. The risk from those geo-hazards induced by earthquake is also high. Community mobilization with activities of regular monitoring of those hazards, skill development for rescue operation, design and implementation of mitigation measures are some of the efforts necessary for better management of disaster risk.